Electronic structures of metallic transition metal dichalcogenides studied by angle-resolved photoemission spectroscopy - Li, Y (2019)
In this thesis, we describe the study on the electronic structures of three selected metallic transition metal dichalcogenides (TMDs) using angle-resolved photoemission spectroscopy (ARPES) as follow: 1. 2H-TaSe2 is a quasi-two-dimensional TMD hosting a 3×3 commensurate charge-density-wave (CDW) at low temperature. Using high-resolution ARPES, we have mapped out the reconstructed electronic structure in the CDW phase. The observation of the fine structure near Brillouin zone (BZ) centre supplements the picture of Fermi surface folding. In addition to the anisotropic CDW band gaps that energetically stabilize the system at the Fermi level in the first-order lock-in transition, we found band reconstruction at high binding energy, which can be well explained by the hybridization between main bands (MBs) and folded bands (FBs). In contrast to the perfectly nested quasi-one-dimensional system, triple-nesting-vector-induced CDW FBs increase the degeneracy of the band crossing and thus further enlarge the magnitude of band gap at certain momentum-energy positions. The visualization and modelling of CDW gaps in momentum-energy space reconciles the long-lasting controversy on the gap magnitude and suggests an electron-phonon coupling mediated Peierls physics in the system. 2. 1T-PtSe2 has recently been proposed to host type-II Dirac fermions. They are Lorentz-violating quasiparticles marked by a strongly tilted conic dispersion along a certain momentum direction and therefore have no analogues in the standard model. Using high-resolution ARPES, we systematically study the electronic structure of 1T-PtSe2 in the full three-dimensional Brillouin zone. As predicted, a pair of type-II Dirac crossings is experimentally confirmed along the kz axis. Interestingly, we have observed conic surface states around time-reversal-invariant momenta Γ̅ and M̅. The signatures of nontrivial topology are confirmed by the first-principle calculation, which shows an intricate parity inversion of bulk states. Our discoveries not only contribute to a better understanding of topological band structure in 1T-PtSe2 but also help further explore the exotic properties, as well as potential application, of group X TMDs. 3. 2M-WS2 has recently been reported to exhibit the highest superconducting transition temperature Tc of 8.8 K among all pristine TMDs. Furthermore, first-principle calculation indicates a nontrivial band structure with a single surface Dirac cone at Γ̅. The coexistence of topological surface state and superconducting phase make it a promising topological superconductor candidate. Using micro-ARPES and high-resolution ARPES, we can distinguish the 2M phase from the trivial semiconducting 2H phase. The ARPES measured electronic structure is in general consistent with the ab initio calculation and shows some signatures of the topological surface states. However, to acquire stronger evidence for topological superconducting phase, high-resolution ARPES measurement on high-quality pure 2M-phase samples is required in the future.